Influence of Social Skills on Students' Mathematical Representation Ability - Izzati, Nurma; Maula, Minhatul (Indonesian Journal of Mathematics Education, 2025)
Social skills play an important role in mathematics learning because they support communication, collaboration, and the presentation of ideas. At the same time, mathematical representation is a key process in expressing concepts in verbal, visual, and symbolic forms. This study aims to determine the influence of social skills on students' mathematical representation ability. A quantitative approach with a one-shot case study design was employed. The population consisted of 605 of an elementary school students at Cirebon, Indonesia in the 2024/2025 academic year, and a cluster random sampling technique was used to select 31 students as the sample. Data were collected through a mathematical representation test and a social skills questionnaire. The results showed that social skills significantly influence students' mathematical representation ability, contributing 67.5%, while the remaining 32.5% is explained by other factors. The regression analysis produced a coefficient of 0.775, indicating that for every one-unit increase in the social skills, the mathematical representation ability score is predicted to increase by 0.775 units. These findings emphasize the importance of developing social skills to enhance mathematical representation and create more effective learning experiences.